Transformasi Tokoh Perempuan Dalam Novel dan Film Serial Gadis Kretek - Perlita, Devina Anabel (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This type of research uses a qualitative descriptive method. Analysis of the data obtained is in the form of words, images, or behavior and is not expressed in the form of numbers or statistical figures, but by providing an explanation or description of the situation or conditions studied in the form of a narrative description. The subject of this research is Ratih Kumala the author of the novel Gadis Kretek and Kamila Andini and Ifa Ifansyah as serial film directors Gadis Kretek. Researchers have a role starting from the planning, implementation and reporting stages of research results. The research carried out was research in the form of novel texts and serial films. To make it easier for researchers to carry out research, an analytical instrument was prepared as a guide for data collection. The results of this research are a form of transformation of female characterizations in the novel Gadis Kretek Ratih Kumala's Works and Film Series Gadis Kretek The work of Kamila Andini and Ifa Isfansyah and knowing the forms of gender injustice in their novels and film series.